Assessment of the dose load during the dismantling of the WWR-M reactor - Yu. M. Lobach; S. Yu. Lobach; E. D. Luferenko; V. M. Shevel (Ядерна фізика та енергетика)
The WWR-M is a light-water-cooled and moderated heterogeneous research reactor with a thermal output of 10 MW. The final decommissioning planning is in progress now. The general decommissioning strategy consists of the dismantling and separate removal of the bulky elements as a whole (in one piece) without preliminary segmentation. The dismantling of the primary and secondary cooling loops is considered as one of the key tasks; a separate dismantling design has been developed. The baseline principles for the technical solution and safety are presented in the given paper. Results of the dose assessment showed that the work can be performed at a collective dose of less than 20 man-mSv.